Elimination of gender equality in Margaret Atwood's The handmaid's tale - Kiss, Beatrix (ELOPE (Ljubljana), 2020)
This paper explores the elimination of equality in The Handmaid's Tale in four areas, called the "4Ds": distinction, dependence, division and dominance. Distinction is a biological point of view in which the Handmaids' fertility becomes the foundation of their victimization. Dependence analyzes turning fertility into their obligation, integrating Foucault's "socialization of procreative behavior", leading to dependence on men. Division entails the physical division of Gilead into subgroups - Handmaids, Wives, etc. - along with the mental division created by distrust among people, harnessed to forestall rebellion. The last area, Dominance, connects the previous areas. Judith Butler's idea that "the body is a variable boundary", shows that the political power over the Handmaids' bodies equals dominance over society and the future, too. The article ends with the conclusion that destruction of women's rights eventually erases the notion of "woman".
Keywords: Atwood v poznejšem obdobju; Atwood, Margaret; digitalna tehnologija; distopija; division of labour; gender equality; gender segregation; oppression; patriarchy; pop-proza; proza po letu 2000; the body; women's rights